Das Alter – ein Problem oder eine Chance? Versuch einer multiperspektivischen pastoralen Reflexion - Dziedzic, Jan ca. 20./21. Jh. (Analecta Cracoviensia, 2011)
Demographic prediction, especially in Europe, indicate considerable increase in population over the age of 65. In the following years the population at generative age will be decreasing. This situation requires specific decisions from the part of a state, society and the Church. Multidimensional support to elderly people can improve the quality of their life and help to respect their dignity. Individual approach to those people is also very important. It may help to their personal (spiritual) development. This paper presents some data from sociology, psychology and theology which may be useful to integral support to an aged person. Assistance the Church offers to elderly people is not restricted to liturgical and/or pastoral care. The Church in cooperation with many other institutions runs residential homes, hospices, seniors clubs, financial support and universities (special courses) for older adults. The purpose of this paper is to better understand the needs of elderly people and to contribute to the betterment of the professional assistance to this social group.